High-Fidelity Simulation Scenario: Pediatric Sulfonylurea Overdose and Treatment - Vincent Calleo; Jacob Anderson; Patrick Curtin; William Paolo (Association of American Medical Colleges, 2020)
Introduction Oral antidiabetic medications are becoming increasingly popular as the incidence of type II diabetes mellitus increases. Overdoses of these medications, either intentional or accidental, can be detrimental if not quickly recognized and treated. One of the most common classes of hypoglycemic oral antidiabetics, sulfonylureas, was discussed in this case. Methods We designed this high-fidelity simulation to help increase the learner's knowledge of sulfonylurea overdoses, including recognizing signs/symptoms, management, and disposition. This simulation was designed to be used with fourth-year medical students, emergency medicine residents, and pediatric residents. The case involves a previously healthy 3-year-old male presenting with altered mental status and seizures secondary to glyburide ingestion. A standard pediatric simulation mannequin was required. The patient presented with altered mental status and began seizing upon arrival. After a thorough history, glyburide ingestion was identified. Critical actions included obtaining a fingerstick glucose measurement, determining an appropriate concentration of dextrose, starting a dextrose drip, and admission for further management. Results This simulation case was performed at the simulation lab at SUNY Upstate Medical University by a combination of 83 fourth-year medical students, and emergency medicine and pediatric residents. Feedback and evaluations for the case showed it improved medical education and clinical skills. Discussion This simulation was well received and helped participants develop a better understanding of sulfonylurea overdose identification. It also improved participants' ability to manage refractory hypoglycemia and compile a more comprehensive list of differential diagnoses.